How academic enjoyment affect achievement in Chinese EFL context: The role of organizational strategies and engagement - Yajun Wu; Xia Kang (Universitas Jambi, Magister Program of English Education Department, 2022)
Academic enjoyment, a positive emotion obtained from engaging in academic tasks, is positively related to the key indicators of academic outcomes, including learning strategy, academic engagement, motivation, and achievement. However, more studies are needed to understand the association between academic enjoyment and achievement, especially in the field of teaching English as a foreign language (EFL) in the Chinese context. This study aimed to investigate the mediating roles of organizational strategies and behavioural engagement in the relationship between academic enjoyment and EFL achievement. Data were collected from 499 Chinese secondary EFL learners during the seventh and eighth grades. Structural equation model (SEM) analyses found that academic enjoyment was positively linked to EFL achievement through the mediating roles of organizational strategy, behavioural engagement, and their chain relationship. The findings sorted out the theoretical framework of “academic enjoyment → organizational strategy → behavioural engagement → achievement”. Limitations and implications are discussed.